Cultural resource management : a collaborative primer for archaeologists - King, Thomas F.; Adekola, Kolawole; Allen, Sarah Caitlin, 1994-; Awe, Jaime J.; Bach, Jaime Lynn; Ward, Katherine Bracken; Farrell, Nancy; Gray, Jay W.; Hawkins, Rebecca A.; Johnson, Dawn; Karl, Raimund; Mattson, Hannah; et al. (Berghahn, 2020)
"Stressing the interdisciplinary, public-policy oriented character of Cultural Resource Management (CRM), which is not merely "applied archaeology," this short, relatively uncomplicated introduction is aimed at emerging archaeologists. Drawing on fifty-plus years' experience, and augmented by the advice of fourteen collaborators, Cultural Resource Management explains what "CRM archaeologists" do, and explores the public policy, ethical, and pragmatic implications of doing it for a living"--